Impact of dry extract of ginger on morphological state of pancreas of syrian golden hamsters on the background of hypercalorium diet - Kononenko, Nadiia; Sorokina, Mariia; Larianovska, Julia; Chikitkina, Valentina (ScienceRise: Pharmaceutical Science, 2018)
The aim is to study the effect of dry extract of ginger on the morphological state of the pancreas of Syrian golden hamsters against the background of a metabolic syndrome induced by a hypercaloric diet. Materials and methods. The metabolic syndrome was modeled with the help of golden male hamsters, 20 weeks old, that had a hypercaloric diet enriched with energy sources (including 29% fat - predominantly saturated lipids) and fructose (1 g per 100 g body weight) for 6 weeks. Dry extract of ginger in a dose of 80 mg/kg, species "Arphasetin" at a dose of 16 ml/kg and metformin tablets at a dose of 60 mg/kg were administered intragastrically once a day, starting at 4 weeks of experiment for 14 days. On the histological sections of the pancreas, the total number of pancreatic islets in the micropreparation was determined, their area was measured, the islets were divided into small, medium and large, and the percentage of each category of pancreatic islets was determined. Results. Prolonged consumption of food rich in fat and carbohydrates by hamsters leads to the development of the state of prediabetes, which is characterized by the morphological inhibition of the insular apparatus: an increase in the relative proportion of small and a decrease in the proportion of medium pancreatic islets, a decrease in availability. According to the morphological characteristics, the introduction of a dry extract of ginger at a dose of 80 mg/kg to hamsters with a metabolic syndrome restores the state of pancreatic islets, their area, β- and α-cells of the pancreas to the level of intact animals. The pharmacological effect of the dry extract of ginger is most likely due to the phenolic compounds that make up its composition - gingerol and shogaol, which may modulate the release of insulin due to the antioxidant effect. Conclusions. According to the severity of the protective action, the dry extract of ginger exceeds the reference preparations - metformin at a dose of 60 mg/kg and the species of "Arphasetin" in a dose of 16 ml/kg. The obtained results testify to the prospects of further experimental and clinical study of the pharmacological properties of dry extract of ginger with the aim of creating an effective antidiabetic phytopreparation